IDENTIFIKASI TEKANAN REKAH KRITIS PADA SUMUR AA-1 DAN AA-2 LAPANGAN PANASBUMI RANAU DEDAP, SUMATERA SELATAN - Artyanto, Andika; Sapiie, Benyamin; Abdullah, Chalid Idham; Sidik, Ridwan Permana (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2019)
Rantau Dedap Geothermal Field is located at about 225 km to the southwest of Palembang City. This field is located on the Semangko Fault, so numerous complex fault and fracture structures formed. Identification of critically stressed fracture used to fracture that has the ability to drain the fluid. Therefore, this analysis needs to be done to geothermal exploration and development on Rantau Dedap Geothermal Field. Rantau Dedap Geothermal Field is controlled by strike slip fault regime shown in at AA-1 and AA-2. Based on critically stressed fracture analysis is known that fracture at AA-1 and AA-2 in critical condition the direction NE-SW on the AA-1, and N-S and NE-SW at AA-2. This indicates that the Rantau Dedap Geothermal Field has a strike slip fault are in critical condition so that it can drain the fluid properly.